1998
DOI: 10.1149/1.1838834
|View full text |Cite
|
Sign up to set email alerts
|

Sulfamides and Glymes as Aprotic Solvents for Lithium Batteries

Abstract: In view of the high reactivity of the lithium metal, lithium batteries must operate in an aprotic environment, which can either be a conducting polymer; a liquid solvent, or a mixture of them. Two families of aprotic liquids were considered as solvents for lithium bis(trifluoromethylsulfone)imide (LiCF3SO2NSO2CF3 or LiTFSI). The first one is the substituted sulfamides, R1R2NSO2NR3R4, where the R groups are either methyl, ethyl, or methoxyethyl (CH,CHOOCH,), and the second one is the glymes, CH3O(CH2CH3O)CH3, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 4 publications
3
70
0
Order By: Relevance
“…Given the maximum ionicity results from an [O]/[Li + ] ratio of ∼4 or 5, these ratios may be sufficient for the dissociation of the solvated Li + and [TFSA] − . In a fashion similar to the mixtures of aprotic ILs and low-polarity solvents, further addition of glymes or THF with low permittivity (ε = 7−8) 56 Such behavior is common for the oligoethers studied in this work. However, this is probably not the case for other nonaqueous aprotic solvents with higher permittivitysuch as PC (ε ∼ 64)where Coulombic attractions between the solvated cation and the counteranions are more shielded.…”
Section: Resultsmentioning
confidence: 76%
“…Given the maximum ionicity results from an [O]/[Li + ] ratio of ∼4 or 5, these ratios may be sufficient for the dissociation of the solvated Li + and [TFSA] − . In a fashion similar to the mixtures of aprotic ILs and low-polarity solvents, further addition of glymes or THF with low permittivity (ε = 7−8) 56 Such behavior is common for the oligoethers studied in this work. However, this is probably not the case for other nonaqueous aprotic solvents with higher permittivitysuch as PC (ε ∼ 64)where Coulombic attractions between the solvated cation and the counteranions are more shielded.…”
Section: Resultsmentioning
confidence: 76%
“…These results further stimulated the infrared study of poly(ethylene oxide)-lithium triflate films, and enabled a more mechanistic understanding of polymer electrolyte materials. To provide an aprotic environment for lithium batteries, Choquette et al 160 studied the phase diagrams, potential windows, conductivities and the lithium interfacial resistances of Li[Tf 2 N] dissolved in sulfamides and glymes. They suggested that glymes or their mixtures with sulfamides could be useful for batteries whose cathode is not a 2D layer structure.…”
Section: Electrochemical Applicationsmentioning
confidence: 99%
“…Poly(ethylene glycol)dialkyl ethers (i.e., R1O(CH2CH2O)nR2), known as end-capped glymes, are characterized by a high flash point and suitable features as aprotic solvents for lithium salts [9]. However, glyme-based electrolytes have revealed poor electrode passivation properties, which limit their application in rechargeable Li-battery due to continuous solvent decomposition by cell operation [10,11].…”
Section: Introductionmentioning
confidence: 99%